Index Method for Assessing Structural Changes in the Economy: Issues of Theory and Practice - T. N. Belova (Статистика и экономика)
Purpose of the study. The article is devoted to the consideration of the most important tools of economic and statistical analysis - indexes of structural changes by Ryabtsev, Gatev and Salai.   The relevance of such work is due to the significant value of using indexes of structural changes that allow making an interconnected analysis of the composition and structure of a phenomenon, taking into account its dynamics.  The purpose of the study is to develop a scale for assessing the significance of structural changes for economic phenomena.   Materials and methods. Foreign trade statistics were used as the database for the empirical study: exports and imports for the Russian Federation as a whole, exports and imports of food by participating countries, imports of certain types of food by countries. The development of a scale for assessing the indexes of structural changes included: firstly, a comparison of the assessment results using the Ryabtsev, Gatev and Salai indexes based on observation data; secondly, the construction of aligned values (trends) for ranked series according to the Ryabtsev, Gatev, Salai indexes; thirdly, comparison of the alignment results and construction of the required scale for assessing measures of the significance of structural changes. An exponential function was used for alignment.   Research results. Based on the results of the study, evaluation scales for the Gatev and Salai indexes were proposed, preserving the verbal characteristics of the Ryabtsev index. The implementation of a methodology based on the alignment of ranked series of values of structural changes indexes made it possible not only to compare different indexes for the same structures of economic phenomena, but also to identify some patterns and features of the use of each of the studied indexes for assessing economic phenomena. With the same range of variation from 0 to 1, the Gatev index is slightly higher than the Ryabtsev index, and the Salai index occupies an intermediate position between the Ryabtsev and Gatev indexes. The author warns against erroneous values of the Salai index, found in some structures. To assess economic structures, which are usually very inertial, the author recommends using the Gatev index, in contrast to the very common Ryabtsev index. With the same components, the Gatev index takes on larger values, the scale “stretches”, and it is more convenient to mark the results of calculations on it.   Conclusion. The use of indexes of structural changes by Ryabtsev, Gatev and Salai, supplemented by a developed scale for assessing the significance of these changes, not only complements the traditionally established procedures of economic analysis, but also deepens it, allows us to find changes in the composition and structure of the phenomenon, determine the direction and significance of these changes.